Experimental Analysis of Composite-to-geopolymer Bonded Structures Using Pull off Tests - Passos,A. C. (2021)
Abstract Composite materials are employed as an alternative of conventional materials due their attractive properties, such as, environmental resistance and high strength-to-weight ratio. However, a limitation to the application of the composites is the low resistance to high temperatures, due their polymeric matrix. Alternatively, geopolymers are inorganic polymers used mainly instead Ordinary Portland Cement (OPC) in civil engineering. They combine good mechanical properties, corrosion resistance and thermal stability, allowing the use as a thermal barrier. This work regards the combined application of composites and geopolymers through adhesive bonding. The main objective is to evaluate the effect of adhesive type and surface treatment on the adhesion between geopolymer and composite pultruded substrates. Pull off tests were carried out in composite-adhesive-geopolymer sandwich specimens. Different surface treatments were examined: unidirectional abrasion and bidirectional abrasion. Specimens were bonded either with an epoxy or a polyurethane adhesive. The influence of the geopolymer manufacturing process on the performance of the structure was also observed.